Some thinking about the academic professors - Parra-Sandoval, María Cristina (Universidade Estadual Paulista / UNESP, 2009)
One of the main characteristics of the Social Sciences at the beginning, of the 21st century is the recovery of the individual. From this point of view, it is very relevant the analysis of the academic professors as the agents that build the institution in which they develop their social life. The aim of this paper is to establish some relation between the theoretical debate and the academic job in its most specific aspects: 1° it is considered as an employment, 2° as an employment, it has a salary paid by the state or by a private institution, 3° it means that they have to meet in unions to negotiate salaries and working conditions, and 4° in spite of all those aspects that could be considered adverse, the academic professors can nevertheless have a relative control of their work. In Latin America this question is strongly intensified by the fact that the regional universities have special characteristics that make them different when the time comes for revindication and the maintenance of their status of public employees and philosophers.